EVALUATION PLANNING LIGHTS SIGNALIZED AND DESIGN WEDENING PRINCE STREET SURYANATA - ROAD KADRIE OENING IN SAMARINDA - HADIJAH, SITI (KURVA S JURNAL MAHASISWA, 2014)
SITI Hadijah , NPM : 10.11.1001.7311.006 ,